On-chip Optofluidic Sensors for Marine Environmental Monitoring: Fundamentals, Current Progress, and Future Directions - Samosir, Justin Todo; Cui, Weicheng (European Journal of Applied Sciences, 2025)
Marine observing increasingly demands sensors that are compact, low-power, and reliable under salinity, temperature, pressure, and biofouling. Conventional instruments meet many performance targets but remain bulky, energy-intensive for dense, long-duration deployment. On-chip optofluidic, which integrates microfluidic with optical transduction, offers a path to miniaturize ocean sensing. This review explains the sensing principles relevant to seawater such as refractive index, absorbance/colorimetry, fluorescence, surface plasmon resonance (SPR/LSPR), with brief notes on elastic scattering and fluidic manipulation. It highlights the key seawater parameters (salinity, temperature, pH/alkalinity, nutrients, dissolved metals, and selected contaminants) along with types of architectures by integration levels, focusing on on-chip optical transducers and clearly separating them from microfluidics coupled to external optical cells. In addition, this paper also summarizes representative progress from 2015-2025 across key seawater physicochemical and contaminants targets). Finally, it outlines a conceptual on-chip design that integrates three measurands (urea, salinity, and microplastics) on a single chip, illustrating further capability of optofluidic technology. Overall, the article provides a concise path from principles to field readiness for optofluidic sensors in marine environmental monitoring.